2007
DOI: 10.1152/ajpcell.00224.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cell and animal models of mtDNA biology: progress and prospects

Abstract: Khan SM, Smigrodzki RM, Swerdlow RH. Cell and animal models of mtDNA biology: progress and prospects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 138 publications
0
25
0
Order By: Relevance
“…The main advantage of these cybrids is the ability to investigate whether phenotypes and biochemical changes are related to changes in the nDNA or mtDNA. Furthermore, cybrid models enable the investigation of in vitro and in vivo effects of different mtDNA mutations in cancer cell lines and tumors with the same nuclear background [215]. A possible disadvantage is the dependency on naturally occurring patient mtDNA variations.…”
Section: In Vitromentioning
confidence: 99%
“…The main advantage of these cybrids is the ability to investigate whether phenotypes and biochemical changes are related to changes in the nDNA or mtDNA. Furthermore, cybrid models enable the investigation of in vitro and in vivo effects of different mtDNA mutations in cancer cell lines and tumors with the same nuclear background [215]. A possible disadvantage is the dependency on naturally occurring patient mtDNA variations.…”
Section: In Vitromentioning
confidence: 99%
“…Presently, this technique is used for studying many human disorders, such as cancer , mitochondriopathies (Swerdlow , 2007 ) and neurodegenerative diseases, such as AD (Cardoso et al , 2004 ), PD (Esteves et al , 2008 ) and HD (Swerdlow et al , 1999 ;Ferreira et al , 2010Ferreira et al , , 2011. This approach allows distinct applications, including the study of mitochondrial DNA mutations, assessing the integrity of the transferred mtDNA, compatibility biogenomic and/or mitochondrial abnormalities (Khan et al , 2007 ;Swerdlow , 2007 ) and, more recently, as a platform for the development of new therapies (Trimmer and Bennett , 2009 ).…”
Section: Cybrids: a Model To Study Mitochondrial Biology In Hdmentioning
confidence: 99%
“…The recent development of a protein-based mtDNA transfection (protofection), which utilizes an engineered human mitochondrial transcription factor A (TFAM) protein, provides opportunities to access the mitochondria for therapeutic interventions. 141143 The components of the engineered protein are based on the naturally occurring, non-immunogenic human proteins TFAM and mitochondrial localization sequence/signal (MLS), to target mitochondria. Studies conducted with sporadic PD cybrid cells have demonstrated the potential for this technology to restore respiration, increase mtDNA levels and gene expression, and increase levels of proteins associated with the electron transport chain.…”
Section: Therapeutic Approachesmentioning
confidence: 99%